Pengaruh Beberapa Jenis dan Konsentrasi Larutan Kecambah Kacang-Kacangan Terhadap Viabilitas Benih Padi Kadaluarsa Varietas Inpago 9 - Alda Navira; Jumar Jumar; Tuti Heiriyani (Agroekotek View, 2020)
This research aims to determine the effect of types, concentrations, and interactions between types and concentrations of a solution of bean sprouts on the viability of expired rice seeds Inpago 9 variety. This research began in December 2019 until February 2020 at the Agroecotechnology Production Laboratory of Agricultural Faculty, Lambung Mangkurat University. The method used in this study is two-factor Randomized Block Design (RCBD). The first factor is the type of bean sprout solution consisting of three levels, namely green bean sprout solution (e1), peanut (e2), and cowpea varieties nagara (e3). The second factor is the concentration of the bean sprout solution consisting of five levels, that is 0% (k0), 10% (k1), 20% (k2), 30% (k3), and 40% (k4). The treatment was repeated three times for each treatment, so it becomes 45 experimental units. The results showed that the invigoration of various types of bean sprout can increase the viability of the growth speed and simultaneous growth of expired rice seeds of Inpago variety. The concentration of bean sprout solution had a significant effect in increasing the viability of expired rice seeds of Inpago 9 variety. Treatment types and concentrations interact with each other on the observed growth speed parameters every day for a week and the growth simultaneity is observed on the 6th day. The 10% concentration for every type of bean sprouts solutions is the best treatment for increasing the viability of expired rice seeds Inpago 9 variety.